Formulation, Evaluation And Antibactery Activity Test Of Gastroretentive Mukoadhesive Granul Matrix Earthworm Extract (Lumbricus rubellus) - Magfirah, Magfirah; Alaydrus, Syafika; Tandi, Joni; Utami, Indah Kurnia; Dewi, Niluh Puspita (Program Studi Farmasi Universitas Mandala Waluya, 2024)
Background: Earthworm extract (Lumbricus rubellus) has antimicrobial activity because it produces high levels of the lumbricine compound but is easily denatured in the stomach so that its solubility and biological activity change. Therefore its Application can be developed in the form of gastrorentetif mucoadhesive preparation. Objectives: The purpose of this study was to optimize and evaluate the antibacterial activity of gastroretentive mucoadhesive preparation matrix of earthworm extract (Lumbricus rubellus). Material and Methods: The matrix utilized a preparatory technique of applying wet granulation mucoadhesive polymers such as chitosan, HPMC, and sodium CMC with concentrations determined based on simple lattice design resulting in 7 granule formulas. The granule formulas obtained were then evaluated including flow time and dwell angle tests, particle size distribution tests, compressibility tests, dissolution tests, and antibacterial activity tests. Results: The results showed that the flow rate on the F3 granule formulation met the requirements of flow rate >10 g/s, a consequence of measuring the angle of repose in the F1-F5 formula had good flowability which was below 30o, in contrast to F6 and F7 which had an angle of repose of 30-40o favorable to flowability. The F1-F7 formula was mostly preserved in mesh number 20 sieve with a size of 426-850 ?m, according to the results of particle size distribution utilizing the multistage sieve method, the compressibility index of the F1-F7 granule formula was 10% and the measurement results at the 30 minute showed that the average dissolution of the F1-F3 granules was 97.77%, 97.77%, and 101.22% respectively while the F4-F7 granule formulas did not show slow drug release because at the 30th minute the drug released ranged and the antibacterial activity test of Formula 1-Formula 7 granules is respectively 6 mm, 5.5 mm, 8 mm, 3.5 mm, 4.7 mm, 2.1 mm and 3.3 mm. Conclusions: The results of the evaluation of the characteristics of earthworm extract mucoadhesive gastroretentive granule preparation demonstrated that the preparation met the requirements for granule preparation and exhibited antibacterial properties. Among the seven formulas tested, formula 3 had the highest efficacy of antibacterial activity.